Natural Resource Use, Incomes, and Poverty Along the Rural–Urban Continuum of Two Medium-Sized, South African Towns. (February 2016) - Ward, Catherine D.; Shackleton, Charlie M.
Highlights: Urbanization studies have neglected small- and medium-sized towns. We examine income sources, levels, and poverty along two rural–urban continua. Emphasis is provided to income from natural resources. The contribution of natural resource income is spatially variable, from 0% to 48%. Exclusion of natural resource income increases poverty estimates by 5–11%. Summary: Urbanization is a significant driver of global change, reshaping livelihoods, productive activities, and incomes. Yet, many elements of what are typically regarded as rural activities can be found in urban places and vice versa. We report on the incomes from land- and cash-based activities along the rural–urban gradient of two South African towns. Although the dominant income strategies varied, all households had more than one income source. Use of wild resources and agriculture were common in urban settings, although variable between and within towns. Poverty levels would be 5–10% higher in the absence of natural resource-based incomes.